Hot-embossing of polymeric micro-structures devices - Teo, Benjamin Qingliang. (2009)
With advancement in technology, many devices are now made smaller, more efficient and yet remain cost effective. This is the same for microfluidic devices that are used for lab on chip devices and other laboratory tests. Previously made using silicon, they are costly and require complex method of lithography fabrication. Research has shown that polymers can be used to fabricate the same chip using simpler methods such as hot embossing at a much lower cost.